Development of Contextual-Based Human, Place and Environment Modules for MTs Grade VII Students - Agustina, Emilia (Jurnal Riset Ilmu Pendidikan, 2024)
This study aims to develop a contextual-based learning module on "Humans, Places, and Environment" for seventh-grade MTs students. The development of this module is based on a contextual learning approach that links the material to students' daily lives to enhance their understanding and critical thinking skills. The research method used is research and development (R&D) with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness test was conducted through expert validation and student trials using descriptive analysis and the N-gain test. The results showed that the module achieved a high level of effectiveness, with a significant improvement in students' understanding based on the N-gain test. The module was also deemed suitable for use in the learning process based on validation from subject matter, design, and language experts. Thus, the development of this contextual-based module can serve as an effective alternative teaching material that supports students' independent learning.